2012
DOI: 10.1093/jjco/hys052
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Post-mastectomy Radiotherapy in Breast Carcinoma Patients with T1-2 Tumor and 1-3 Axillary Lymph Node(s) Metastasis

Abstract: Objective: To investigate the role of post-mastectomy radiotherapy in breast carcinoma patients with a tumor size of 5 cm or smaller (T1-2) and 1 -3 axillary lymph node(s) metastasis (N1). Methods: We retrospectively reviewed the file records of 575 patients receiving radiotherapy (452 patients) and not receiving radiotherapy (123 patients). Results: In the whole series, locoregional recurrence-free survival was significantly better in patients receiving radiotherapy compared with patients not receiving radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…Similar result was reported by Duraker et al , who reported fewer removed LN was associated with worse survival 30. An indirect method to evaluate the adequacy of removed LN is the ratio of positive LN of all removed LN 3033. In our analysis, we also found that PMRT can significantly reduce LR in T1–2, N1 breast cancers with ratio > 0.25 of positive LN.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar result was reported by Duraker et al , who reported fewer removed LN was associated with worse survival 30. An indirect method to evaluate the adequacy of removed LN is the ratio of positive LN of all removed LN 3033. In our analysis, we also found that PMRT can significantly reduce LR in T1–2, N1 breast cancers with ratio > 0.25 of positive LN.…”
Section: Discussionsupporting
confidence: 90%
“…Fewer uninvolved LN might be associated with inadequate surgical sampling or pathological examination. Similar result was reported by Duraker et al , who reported fewer removed LN was associated with worse survival 30. An indirect method to evaluate the adequacy of removed LN is the ratio of positive LN of all removed LN 3033.…”
Section: Discussionsupporting
confidence: 80%
“…Kong et al (2013) reported that histologic grade 3 and extracapsular extension were significant predictive factors for SCFR. Duraker et al (2012) reported lymph node ratios > 0. 25 in patients with T1N1 breast cancer and >0.…”
Section: Discussionmentioning
confidence: 99%
“…2% in patients with 1-3 positive ALN without RT (Strom et al, 2005;Macdonald et al, 2009;Yu et al, 2010;Yates et al, 2012;Grotenhuis et al, 2013;Yu et al, 2013). In addition, SCFR may increase the incidence of distant metastasis (Fan et al, 2010;Reddy et al, 2011;Duraker et al, 2012), which impacts the quality of life and OS. Currently, the guidelines of NCCN (2011) and DEGRO (SautterBihl et al, 2008) recommend supraclavicular radiation therapy (SCRT), but the NZGG recommends SCRT only in patients with ≥4 positive ALN.…”
Section: Introductionmentioning
confidence: 99%
“…Truong et al 15 suggest that the percentage of positive lymph nodes rather than the number should be used to guide decision making with regards to post-mastectomy radiotherapy. Duraker et al 16 made a similar recommendation, based on their study of 575 women with T1-2 tumours and 1e3 positive lymphnodes. In this study, lymphnode ratio was defined as the ratio of the number of metastatic lymph nodes to the number of removed lymph nodes.…”
Section: Indications For Postmastectomy Radiotherapymentioning
confidence: 94%